Insights into the Scholl Coupling Reaction: A Key Transformation of Relevance to the Synthesis of Graphenes and Related Systems. Issue 13 (30th January 2017) - Little, Mark S.; Yeates, Stephen G.; Alwattar, Aula A.; Heard, Kane W. J.; Raftery, James; Edwards, Alyn C.; Parry, Adam. V. S.; Quayle, Peter
Abstract : The Scholl‐type reactions of 4, 10‐disubstituted chrysene derivatives proceeded by variegated and unexpected oxidation/coupling pathways. These observations serve as a cautionary note when attempting to employ the Scholl reaction in target‐oriented materials synthesis. Abstract : Scholl coupling reactions proceed by unexpected oxidation/coupling pathways.